2014
DOI: 10.1038/onc.2014.322
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of Sin3B by Bmi-1 prevents cellular senescence and is relieved by oncogene activation

Abstract: The Polycomb group protein Bmi-1 is an essential regulator of cellular senescence and is believed to function largely through the direct repression of the Ink4a/Arf locus. However, concurrent deletion of Ink4a/Arf does not fully rescue the defects detected in Bmi-1−/− mice, indicating that additional Bmi-1 targets remain to be identified. The expression of the chromatin associated Sin3B protein is stimulated by oncogenic stress, and is required for oncogene-induced senescence. Here we demonstrate that oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…We have previously demonstrated that Sin3b -inactivated cells are refractory to the cell cycle exit elicited upon CDKN2A (P19ARF) overexpression, a well-established inhibitor of the MDM2-driven degradation of TRP53. In addition, we found that SIN3B levels are elevated in PINs in the mouse, consistent with our previous results demonstrating an increase in SIN3B levels upon entry into senescence (12,16,32). We and other groups have demonstrated the requirement for SIN3B to repress E2F target transcription in specific cell cycle exit settings (12,33).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have previously demonstrated that Sin3b -inactivated cells are refractory to the cell cycle exit elicited upon CDKN2A (P19ARF) overexpression, a well-established inhibitor of the MDM2-driven degradation of TRP53. In addition, we found that SIN3B levels are elevated in PINs in the mouse, consistent with our previous results demonstrating an increase in SIN3B levels upon entry into senescence (12,16,32). We and other groups have demonstrated the requirement for SIN3B to repress E2F target transcription in specific cell cycle exit settings (12,33).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we have recently determined that the polycomb group protein BMI1 directly represses the transcription of the SIN3B locus, similar to what has been observed for the INK4A/ARF locus (32,36,37). Consistently, ectopic expression of BMI1 in tandem with Pten inactivation in the mouse prostate leads to invasive PCa (38).…”
Section: Discussionsupporting
confidence: 77%
“…Specifically, Sin3B-deleted pancreata developed KRas-driven early pancreatic lesions with an increased latency compared to their Sin3B-expresing counterparts, and these lesions progressed much more slowly to adenocarcinoma. Importantly, Sin3B inactivation appeared to prevent the occurrence of cellular senescence in early pancreatic preneoplastic lesions, consistent with previous studies demonstrating its central role in oncogene-induced senescence (DiMauro et al, 2015;Grandinetti et al, 2009). Senescent cells are known to secrete a set of inflammatory cytokines collectively referred to as the SASP (or senescence-associated secretory phenotype) (for a review, see Rodier & Campisi, 2011).…”
Section: Sin3b Promotes Senescence-associated Inflammation and Pancresupporting
confidence: 75%
“…At the transcription level, a recent report has shown that Sin3B is repressed by polycomb group protein Bmi-1. In this study the authors show that Bmi-1-driven repression of Sin3B is relieved by oncogenic stress that results in onset of senescence (DiMauro, Cantor, Bainor, & David, 2015). Sin3B also interacts with an E3 ubiquitin ligase, RNF220 that targets Sin3B for ubiquitination and promotes its proteasomal degradation (Kong et al, 2010).…”
Section: Expression and Regulationmentioning
confidence: 97%
“…[15][16][17] Consistent with these biochemical properties, Sin3B is required for quiescence upon serum starvation and for cellular senescence upon oncogene activation or serial passaging in mouse embryonic fibroblasts. 15,18,19 These experiments indicate that Sin3B modulates cell cycle withdrawal and differentiation in somatic cells. However, whether Sin3B controls cell cycle withdrawal in stem cells has not been investigated.…”
Section: Introductionmentioning
confidence: 86%